KERJA SAMA INDONESIA - UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) DALAM MENANGANI KEKERASAN BERBASIS GENDER DI PAPUA, INDONESIA (2016 - 2020) - Yona Melina, (2023)
This research aims to look at the implementation and role of cooperation between Indonesia and USAID in dealing with gender-based violence that has occurred in Papua, especially for women in Papua who are related to IDG in two districts of Papua Province, namely Jayapura and Jayawijaya, using the theory of international cooperation and violence. gender-based reference to CEDAW. The author explains how participation is realized in this study, the factors that underpin the violence in Papua, the condition of IDG in Jayapura and Jayawijaya prior to cooperation, and the challenges and obstacles for USAID in assisting with the violence in Papua. The research method used is descriptive-qualitative, using data sources, namely primary and secondary data. The primary data collection technique is based on interviews and secondary data, specifically the results of a literature review. The final results of this research show that the cooperation between Indonesia and USAID in dealing with gender-based violence in Papua is considered successful. Even though in 2020 the whole world was shaken by the discovery of a pandemic, USAID was able to slowly overcome it.